LINGUO-AREAL MAPPING OF THE LEXICON OF UZBEK AND TAJIK DIALECTS IN EASTERN SURKHANDARYA - Saidova Sayyora Eshonqulovna (International Journal of Literature and Language Studies, 2026)
This article examines the linguo-areal mapping of lexical units in Uzbek and Tajik dialects spoken in Eastern Surkhandarya. The region is characterized by long-term ethnic, cultural, economic and linguistic contact between Uzbek- and Tajik-speaking communities. Such contact has created a complex dialectal environment in which lexical units, synonymous forms, borrowings, semantic shifts and local nominations are distributed unevenly across villages, mountain areas, foothill settlements and rural speech communities.